A brief historical overview and technical and legal framework for the exercise of government administration - Bolaños-Garita, Rolando (2012)
The ability to lead a state apparatus, regardless of the country in question, involves a number of specific characteristics that must be understood by public officials at all levels, both those at the pinnacle of the political hierarchy and those at more operational or administrative levels. In the case of Costa Rica, although a comprehensive theoretical, legal, technical and, if you will, socio-historical framework exists, the exercise of government leadership has not yet been fully consolidated, and so a brief examination of some of the considerations surrounding this subject is expected to prove useful to all those involved in government decision-making, as well as to researchers and scholars of the phenomenology of public administration.